CALIFORNIA FOLLOW-UP. - NIELSEN VG JR; DOBBS NIELSEN (Tufts Archival Research Center, 2007)
Marginalia; Letter to John Kelly, Vice President of the Tobacco Institute, from Dobbs & Nielsen Attorneys. Summarizes thoughts on how to follow-up on the 1978 tobacco industry investment in California. Outlines and describes steps. Recommends conducting an independent inventory of the investment and creating a visible key California contact. Discusses an immediate short-range program and considerations for a long term program. Lists organizations with whom to establish stronger ties.